Stability-Centric Design of a Droop-Mounted Adaptive Nonlinear Control for EV Charging in DC Microgrid - Aqeel Ur Rahman; Nicola Campagna; Filippo Pellitteri; Antonino Oscar Di Tommaso; Rosario Miceli (IEEE Access)
This paper presents a streamlined two-layer control system for effective power sharing and switching control in a DC microgrid designed for electric vehicles. The system integrates Energy Storage Systems and advanced converters to ensure a broad operational range and bidirectional power flow. The Dual active bridge topology is used to integrate the EV to DC MG. Hence, the DC MG system has multiple power converter operating simultaneously. The enhanced droop control strategy is advised for the upper layer and the switching controller is derived using nonlinear controls theory embedding the barrier functions. The enhanced droop strategy shares the power considering the individual dynamics of the storage devices while Barrier-based sliding mode control is applied to converters for current/voltage tracking. Mathematical analysis, leveraging Lyapunov’s theory, confirms the large signal stability of the system. Demonstrated through MATLAB/Simulink-based simulations, the control system exhibits proficient load power sharing, and the adaptive nonlinear controller showcases robustness against unforeseen disturbances. Moreover, the comparative analysis provides insight into the performance of the proposed control methods concerning traditional methods. Hardware-in-loop tests, utilizing Typhoon HIL 404, authentically validate the real-time performance of the proposed control strategies. Different EV and Constant Power Load scenarios ensure a thorough examination, supporting the efficacy of the system. The study contributes valuable insights into the feasibility and efficiency of these control strategies, paving the way for advancements in sustainable electric mobility.